Hydropower in authoritarian Brazil an environmental history of low-carbon energy, 1960s-1990s - Johnson, Matthew P. (Studies in environment and history, 2024)
During the later twentieth century, Brazil's right-wing military dictatorship built a vast network of hydropower dams that became one of the world's biggest low-carbon electricity grids. Weighed against these carbon savings, what were the costs? Johnson unpacks the social and environmental implications of this project, from the displacement of Indigenous and farming communities to the destruction of Amazonian biodiversity. Drawing on rich archival material from forty sites across Brazil, Paraguay, and the United States, including rarely accessed personal collections, Johnson explores the story of the military ofﬁcers and engineers who created the dams and the protestors who fought them. Brazilian examples are analyzed within their global context, highlighting national issues with broad consequences for both social and environmental justice. In our race to halt global warming, it is vital that we learn from past experiences and draw clear distinctions between true environmentalism and greenwashed political expedience